2018
DOI: 10.1159/000494441
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Risk Factors Including Bone-Derived Biomarkers and Aortic Arch Calcification in Maintenance Hemodialysis Patients

Abstract: Background/Aims: Aortic arch calcification (AoAC) is frequently detected in maintenance hemodialysis (MHD) patients and is associated with cardiovascular and all-cause mortality. We investigated the factors associated with AoAC and analyzed the relationship between the factors including bone-derived biomarkers and AoAC. Methods: We enrolled 389 stable MHD patients. AoAC was assessed using chest-X ray examination. Demographic data was collected in addition to serum levels of biochemical and bone-derived biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
(39 reference statements)
0
10
0
1
Order By: Relevance
“…At present, there is no good index to reflect the pathophysiological mechanism of vascular calcification, and guide clinical diagnosis and treatment. The classical markers, such as serum calcium ( 17 ), serum phosphorus ( 18 ), PTH ( 18 ), AKP ( 19 ) and FGF23 ( 20 ), are not specific and sensitive enough to reflect the pathophysiologic mechanisms underlying the process of VC ( 21 ). A review focuses on the pathophysiological mechanisms of vascular and valvular calcification in general population, list OC as one of the promoters in a table.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there is no good index to reflect the pathophysiological mechanism of vascular calcification, and guide clinical diagnosis and treatment. The classical markers, such as serum calcium ( 17 ), serum phosphorus ( 18 ), PTH ( 18 ), AKP ( 19 ) and FGF23 ( 20 ), are not specific and sensitive enough to reflect the pathophysiologic mechanisms underlying the process of VC ( 21 ). A review focuses on the pathophysiological mechanisms of vascular and valvular calcification in general population, list OC as one of the promoters in a table.…”
Section: Discussionmentioning
confidence: 99%
“…OC is positively correlated with phosphorus, iPTH, FGF23 and AACs, but the multiple logistics regression analysis revealed that only age and OC(OR=1.10, P=0.008)were risk factors for high AACs (≥5). There have been studies in dialysis patients showed increasing VC severity with age, regardless of factors such as dialysis vintage, dyslipidemia, PTH level and hypertension ( 21 ). It can be said that the effect of age on vascular calcification is well recognized.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the presence and progression of AoAC are strong risk factors for cardiovascular morbidity and mortality [ 28 , 29 , 30 ]. The etiology of VC is multifactorial in patients with ESRD, and it has been reported to involve aging, diabetes, smoking, oxidative stress, inflammation, hyperfibrinogenemia, dysregulation of fibroblast growth factor 23, intact parathyroid hormone, calcium and phosphorus, protein-energy wasting, loss of osteopontin and fetuin-A, the osteoprotegerin/receptor activator of NF-kB/receptor activator of the NF-kB ligand system, as well as an increase in sclerostin [ 31 , 32 , 33 ]. In addition, apoptosis and osteochondrogenic differentiation of vascular smooth muscle cells have also been shown to play important roles in arterial medial calcification, which can induce tunica media remodeling and increase arterial stiffness and reduce vascular compliance [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The progression of vascular calcification has been associated with factors including aging, diabetes mellitus, inflammation, oxidative stress, uremic toxins, the renin-angiotensin system activity, high blood pressure, hyperlipidemia, and mineral disorders [25]. Hyperphosphatemia is considered the main factor in the pathophysiology of AoAC [26].…”
Section: Discussionmentioning
confidence: 99%